Spiritual intelligence and professional nursing practice: A systematic review and meta-analysis - Amir Masoud Sharifnia; Ritin Fernandez; Heidi Green; Ibrahim Alananzeh (Elsevier, 2022)
Background: The concept of spiritual intelligence was developed in 1997 based on philosophical theories and neurological evidence and introduced as the ultimate intelligence. Spiritual intelligence has been considered as one of the skills required by professionals and has recently gained traction within nursing practice. Understanding the role of spiritual intelligence and its association with professional nursing practice is crucial to creating knowledge in this area of inquiry. Objective: To identify the best available evidence of the spiritual intelligence level and its correlation with professional practice among nurses. Design: A systematic review and meta-analysis of observational studies were reported according to the PRISMA and MOOSE guidelines. The protocol for this systematic review was registered with PROSPERO with the identification CRD42021254881. Data Sources: Ten electronic English and Persian databases [Cochrane Library, Web of Science, Scopus, PubMed, CINAHL, Science Direct, Wiley Online Library, Magiran, SID, IranDoc] were searched to identify eligible studies, published in the English and Persian languages from January 2000 to May 2020. Review Methods: A systematized search strategy was used to include eligible published and unpublished observational studies that examined the spiritual intelligence level and its correlation with professional practice among nurses. Screening, quality assessments, data extractions, and analysis were undertaken using Joanna Briggs Institute methodology and carried out by two independent reviewers. Results: Thirty-five studies, with a total of 7301 nurses, were included. The mean score for spiritual intelligence in 29 studies and 5853 nurses was 0.63 (95% CI: 0.57-0.69, I2 = 99.97%). The Spiritual Intelligence Self-Report Inventory was the most frequently used instrument to measure spiritual intelligence. Most of the professional nursing outcomes represented a positive association with nurses' spiritual intelligence. The pooled positive correlation coefficients between spiritual intelligence and a professional nursing practice components including the art of nursing, competence, attributes of practice and, personal commitment were 0.34 (95% CI: 0.24, 0.43, I2 = 63.4%, 5 studies), 0.42 (95% CI: 0.25,0.56, I 2 = 62.2%, 2 studies), 0.32 (95% CI: 0.11, 0.50, I 2 = 92.2%, 5 studies) and 0.41 (95% CI: 0.34, 0.49, I 2 = 74.3%, 8 studies) respectively. Conclusions: The findings of this systematic review indicated a relatively high level of spiritual intelligence among nurses that was moderately associated with professional nursing practice. implementing strategies to promote spiritual intelligence levels among nurses is warranted.